Shalat as a Solution to Digital Addiction: A Tadabbur Perspective on QS. Al-‘Ankabut: 45 - Haris Renaldi; Budi Suhartawan; St. Fajriani Tahir; Hazem Yousef Aboudeif; Muhammad Iskandar (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2026)
Excessive use of gadgets has a negative impact on mental, social and physical health, and contradicts Islamic principles of respect for time and social care, so it is categorized as a munkar action. Countermeasures are carried out through psychological approaches, such as self-management counseling techniques, as well as spiritual approaches through the implementation of prayer practices referring to QS. Al'Ankabut verse 45 that prayer can prevent from immoral and unlawful actions. The method used is the tadabbur method formulated by Bachtiar Nasir. The results of the study show that prayers that are performed by appreciating the recitation, solemnity, dhikrullah, fulfilling all the conditions and pillars, and maintaining the time of implementation, have a role in shaping individual characters who are able to regulate themselves, become more disciplined, and develop higher concentration and self-awareness in the use of digital devices. Therefore, prayer not only functions as ritual worship, but also has the potential to serve a form of spiritual therapy for addressing gadget addiction.